2009
DOI: 10.1159/000201109
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Serotonin Concentration and Monoamine Oxidase Activity in Hypothyroid Patients

Abstract: Background/Aim: The relationship between the hypothalamic-pituitary-thyroid (HPT) axis and the serotonergic (5-hydroxytryptamine, 5-HT) system is not clear. The aim of the study was to determine platelet biochemical markers (5-HT concentration and monoamine oxidase B, MAO-B, activity) in hypothyroid patients. Methods: The study included 25 medication-free female hypothyroid patients in postoperative follow-up after total thyroidectomy due to papillary thyroid carcinoma, who had not been treated with synthetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 80 publications
1
5
0
2
Order By: Relevance
“…Hassan et al (41) observed that there was a significant decrease of plasma dopamine, norepinephrine, and serotonin levels in young and adult rats with hypothyroidism. A similar decrease in platelet serotonin concentration was also reported in a study conducted on hypothyroid patients (42). Congenital hypothyroidism leads to a lower developmental quotient and delay in psychomotor development as well as to high depression/anxiety scores in clinical samples (13,43,44,45).…”
Section: Discussionsupporting
confidence: 87%
“…Hassan et al (41) observed that there was a significant decrease of plasma dopamine, norepinephrine, and serotonin levels in young and adult rats with hypothyroidism. A similar decrease in platelet serotonin concentration was also reported in a study conducted on hypothyroid patients (42). Congenital hypothyroidism leads to a lower developmental quotient and delay in psychomotor development as well as to high depression/anxiety scores in clinical samples (13,43,44,45).…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, there appear to be links between the HPT axis and personality traits in healthy humans (Arqué et al 1987;Balada et al 1992;Frey et al 2007). Finally, the HPT axis interacts with neurotransmitters, including serotonin and dopamine (Bauer and Whybrow 2002;Stipcevic et al 2009). Therefore, individual variation along the HPT axis has the potential to link energetics with personality.…”
Section: Mechanismsmentioning
confidence: 99%
“…The use of MAO inhibitors in rats can change TSH release patterns, resulting in decreased transport of iodine [6,7]. Thyroid MAO enzyme is involved in the biosynthesis of thyroid hormones due to its ability to produce hydrogen peroxide [8]. When MAO is inhibited, the concentration of potent neurotransmitters such as dopamine increases which exert their inhibitory effects on the release of TSH stimulation via thyrotropin-releasing hormone (TRH) [9].…”
Section: Discussionmentioning
confidence: 99%